1964
DOI: 10.1136/bmj.1.5392.1220
|View full text |Cite
|
Sign up to set email alerts
|

Serum Transaminase Activity in Status Asthmaticus

Abstract: Vacuum Extractor-Chalmers MBICARJOURNAL anterior position. The more experienced practitioner may wish to extend the range of his intervention, but this should be limited to institutional conditions. There are many general practitioners in this country, including several of our former house-surgeons, who are using the instrument successfully. Further extension of this trend would help to reduce the dangers of forceps in unpractised hands and lead to improved figures for infant survival in the home, as we believ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

1965
1965
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…2,4,5 However, others have postulated that altered oxygen supply to the liver may not be the only mechanism, and that the increase in enzyme activity may be mediated by allergic reactions in the lung. 6 A few studies have reported abnormal liver function tests associated with long-term xanthine therapy, 7 long-term systemic corticosteroid use, 8 and with experimental treatment with zileuton, an inhibitor of the enzymatic pathway leading to leukotriene formation.…”
Section: O O R R I I G G I I N N a A L L A A R R T T I I C C L L E E mentioning
confidence: 99%
“…2,4,5 However, others have postulated that altered oxygen supply to the liver may not be the only mechanism, and that the increase in enzyme activity may be mediated by allergic reactions in the lung. 6 A few studies have reported abnormal liver function tests associated with long-term xanthine therapy, 7 long-term systemic corticosteroid use, 8 and with experimental treatment with zileuton, an inhibitor of the enzymatic pathway leading to leukotriene formation.…”
Section: O O R R I I G G I I N N a A L L A A R R T T I I C C L L E E mentioning
confidence: 99%
“…Past attempts to relate increases in serum GOT levels with prognosis in asthma patients have been unsuccessful (El-Shaboury et al, 1964). The present finding of a lack of correlation between the clinical condition of the patient and the various isoenzyme levels, coupled with the further increases noted in certain clinically improved patients, indicates that the more specific assay is equally inapplicable for this purpose.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, centrilobular necrosis has been detected at necropsy in 5% and steatosis in 23% of patients dying from asthma (Colldahl, 1971). El-Shaboury et al (1964), however, found no correlation between serum GOT activity and liver function tests in patients suffering asthma attacks, and suggested that the increase in circulating enzyme activity may have arisen from lung tissue damaged by allergic reaction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The reason for this difference is not known, although one possible explanation would be a difference of disease severity. AST and ALT elevations have been reported in severe asthmatics and hypothesized to reflect hypoxic liver damage during acute status asthmaticus [7][8][9][10][11][12]. Retrospective analyses of health care system data have also revealed higher LFT elevation rates in severe asthma patients [13,14].…”
Section: Discussionmentioning
confidence: 95%